2008
DOI: 10.1086/590051
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Observations of the Type Ib Supernova SN 2006jc: Evidence of Interactions with Dust

Abstract: In the framework of a program for the monitoring of supernovae in the near-infrared (NIR) carried out by the Teramo, Rome, and Pulkovo observatories with the AZT-24 telescope, we observed the supernova SN 2006jc in the J, H, and K photometric bands during a period of 7 months, starting $36 days after its discovery. Our observations evidence a NIR rebrightening, peaking $70 days after discovery, along with a reddening of (H À K) and (J À H) colors until 120 days after discovery. After that date, (J À H) seems t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Given the uncertainties involved in the derivations, it is encouraging to note that these estimates are consistent with the dust masses computed for other SNe IIn (e.g., Gerardy et al 2002;Pozzo et al 2004;Meikle et al 2007;Trundle et al 2009;Andrews et al 2011;Gall et al 2011), and the Type Ibn SN 2006jc (Smith et al 2008b;Di Carlo et al 2008;Nozawa et al 2008;Mattila et al 2008;Anupama et al 2009;Sakon et al 2009). …”
Section: Discussionsupporting
confidence: 71%
“…Given the uncertainties involved in the derivations, it is encouraging to note that these estimates are consistent with the dust masses computed for other SNe IIn (e.g., Gerardy et al 2002;Pozzo et al 2004;Meikle et al 2007;Trundle et al 2009;Andrews et al 2011;Gall et al 2011), and the Type Ibn SN 2006jc (Smith et al 2008b;Di Carlo et al 2008;Nozawa et al 2008;Mattila et al 2008;Anupama et al 2009;Sakon et al 2009). …”
Section: Discussionsupporting
confidence: 71%
“…Dust formation has been observed in SN 2006jc early on, at ∼50 d past maximum (Di Carlo et al 2008; Nozawa et al 2008; Smith et al 2008). Dust formation is reflected in the helium emission line profiles, which developed an asymmetric profile, with the red wing of the profile getting increasingly suppressed with time, and also in the increase in the red to NIR continuum between 65 and 120 d. Smith et al (2008) estimate the dust temperature during this phase to be ∼1600 K. The estimated densities in the shell are high enough to precipitate graphite dust (Clayton 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Within the CDS conditions can allow new dust to form (Pozzo et al 2004). CDS dust has been invoked as the origin of the early-time IR excess of SN 2006jc (Smith et al 2008;Di Carlo et al 2008;Mattila et al 2008). Mattila et al (2008) showed that the IR emission was probably an IR echo from the CDS dust.…”
Section: The Warm Component: Early-phase Ir Excess Due To a Cdsmentioning
confidence: 99%